Musculoskeletal outcomes in children using computers : a model representing the relationships between user correlates, computer exposure and musculoskeletal outcomes - Harris, Courtenay (Curtin University, 2010)
The etiology of musculoskeletal outcomes associated with the use of information technology (IT) has predominately been defined by studies of adults in their work environments. Theories explaining the causation of work related musculoskeletal disorders have identified individual user (biomechanical, physiological and psychosocial), task demand, work organization and environmental risk factors. Models based on these theories have subsequently been developed to investigate the causal relationship between IT exposure and outcomes experienced by the user.Computers are an important IT type used by children, and computer use by children is rapidly growing in both school and home environments. Recent literature demonstrates an increase in children’s reports of computer related musculoskeletal outcomes. Children’s computer use appears to be different to adult’s work related computer use. Thus, although many potential risk factors for children may be similar to those for adults, it is proposed that risk factors and models of causal relationships between computer use and musculoskeletal outcomes may vary for children.The main aims of this study were: (1) to investigate children’s computer exposure in their usual occupational environments of school and home; and (2) to develop and test a multivariable model that would assist in understanding relationships between child user correlates, computer exposure and computer related musculoskeletal outcomes.1351 students (792 boys and 559 girls) from eight primary and five secondary schools in Perth, Australia, participated in the study in 2006. Convenience sampling was undertaken within stratified groups, to ensure the sample had the required range of participants from different socioeconomic status (SES) backgrounds, both genders and school Years 1, 6, 9 and 11(approximate ages 6, 9, 14 and 16 years).The study design was cross sectional involving the completion of a questionnaire survey by participants, and for younger participants their parents. Questionnaires contained items relating to the participant and their activity exposure as an individual, within a family context, and within their neighbourhood. Physical measures of height and weight were also collected.The results showed that 100% of children had access to computers at school, and at home 98.9% of children had access to computers, with 95.9% reporting home internet access. The use of different exposure measures demonstrated that at school 97.8% of children had used a computer in the last month, for an average of 2.4 hours per week, commonly for 30-60 minutes in one sitting. At home 95.7% of children had used a computer in the last month, for an average of 7.2 hours per week, commonly for 60 - 120 minutes in one sitting. Computer activities performed more frequently at school were surfing the internet, learning programs and multimedia. At home the most frequent computer activities were surfing the internet and email. Children with bedroom computer access were found to have nearly 50% greater mean weekly hours of use. The use of a range of computer exposure measures (frequency, usual and longest duration, mean weekly hours and frequency of computer activities) provided better characterization of the amount and nature of children’s school and home computer exposure.Age and gender were associated with children’s school and home computer use. Computer use was greater with age for both boys and girls, and boys had greater use than girls across all Year levels for all exposure measures except school usual duration. Children with greater computer exposure were shown to experience less computer anxiety; reported more somatic complaints; had used a broader range of computer activities; had greater exposure to other IT activities (electronic games, TV, mobile phone) and moderate vigorous physical activity. SES was associated with computer exposure, with children from low SES backgrounds having greater home computer exposure, and children from high SES backgrounds having greater school computer exposure.Computer related musculoskeletal outcomes were reported by 10% of children for school computer use and 20% for home computers. The most commonly affected body locations were the neck and back, and 30% of those children reporting outcomes limited their activity participation, 10% took medication and 7% consulted a treating health professional. The use of a range of outcome measures allowed for a better understanding of the impact of children’s computer related musculoskeletal outcomes.Given the significant findings of different relationships between children’s computer exposure patterns at school and home, two models were developed and tested, with one model for school computer exposure and one model for home computer exposure. Path analysis modeling, accounting for user correlates, tested direct relationships and indirect relationships via computer exposure for a range of user correlates. The final school computer exposure model showed direct relationships between gender, somatic complaints, computer exposure and musculoskeletal soreness; and indirect relationships, via computer exposure, between age, computer flow, TV exposure, SES and musculoskeletal soreness. The final home computer exposure model showed direct relationships between gender, age, somatic complaints, computer exposure and musculoskeletal soreness; and indirect relationships, via computer exposure, between age, computer flow, computer anxiety, TV exposure, SES and musculoskeletal soreness.In conclusion, the child specific model tested within this study demonstrated direct relationships between children’s computer exposure and musculoskeletal outcomes. Additionally, direct and indirect relationships were also shown between a range of user correlates, the environment and musculoskeletal outcomes. These findings will assist researchers, teachers and parents to understand the range of potential risk factors for computer related musculoskeletal outcomes. This will also allow researchers to target interventions to child users and their computer environments to ensure children’s computer use is performed in a safe and productive manner.